Developing nexus eco-purchasing behaviour index (NEPBI) for Malaysia by using partial least square analysis - Rajadurai J.; Wan Hanafi W.N.; Bathmanathan V.; Daud S.; Azami N. (Springer Science and Business Media B.V., 2023)
The use of non-biodegradable products, along with products that deplete natural global resources, has been detrimental to the sustainability of our environment. The Nexus generation is becoming the dominant consumer demographic, but because it will be the main consumer group, its purchasing trends need to be monitored to ensure its consumption patterns do not negatively affect the environment. To address this problem, this study aimed to capture the indicators that represent Nexus Eco-Purchasing Behavior and to establish a Nexus Eco-Purchasing Behaviour Index (NEPBI) using Partial Least Square analysis for Malaysia as a whole and for each of the five zones in Malaysia, namely the Northern, Middle, Southern, Eastern and East Malaysia zones. The study involved a preliminary review of the literature pertaining to Nexus behaviors, a focus group discussion with Nexus, expert opinion interviews, a pilot study and a survey. The indicators used in this study to represent NEPBI are environmentally compatible products, recyclable packaged products, minimal damaging products, more expensive products, eco-labelled green products, environmentally friendly brands and a well-informed green consumer. NEPBI can be used by all stakeholders (government, non-governmental organizations, producers and Nexus consumers) in decision making, especially where it involves resource commitments to encourage eco-purchasing behaviour. Having this index will also enable the Malaysian government to create a pathway to developing a green consumer society prepared to meet the United Nations Sustainable Development Goals under the ambit of Goal # 12 which is to ensure sustainable consumption and production patterns. 2021, The Author(s), under exclusive licence to Springer Nature B.V. part of Springer Nature.